TANGGUNG JAWAB PEMEGANG SAHAM PERSEROAN TERBATAS MENURUT HUKUM POSITIF - Mr Kurniawan (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2014)
Limited Liability Companies have completeness instrument called organ corporation which consists of General Meeting of Shareholders (GMS), the board of directors, and the board of commissioners. According to Commercial Law (KUHD), Act No. 1 of 1995 jo. Act No. 40 of 2007 on Limited Liability Companies, the principle liability of General Meeting of Shareholders (GMS) is limited on their share. But, if it is proven that, among others, there has been a mixing of the shareholder’s personal assets and the Company’s assets, so the limited liability turns into unlimited liability or personal liability. Perseroan Terbatas (PT) memiliki alat kelengkapan yang disebut organ perseroan terdiri dari Rapat Umum Pemegang Saham (RUPS), Direksi dan Dewan Komisaris. Menurut Kitab Undang-Undang Hukum Dagang (KUHD), UU PT No. 1 Tahun 1995 jo. UU PT No. 40 Tahun 2007, tanggung jawab Pemegang Saham (RUPS) pada prinsipnya adalah bersifat terbatas pada saham yang dimiliki. Akan tetapi, apabila dapat dibuktikan bahwa telah terjadi pembauran harta kekayaan pribadi Pemegang Saham dengan harta kekayaan perseroan, maka tanggung jawab terbatas tersebut akan berubah menjadi tanggung jawab tidak terbatas atau tanggung jawab pribadi.